Sorafenib selectively depletes human glioblastoma tumor-initiating cells from primary cultures - Carra, Elisa (Landes Bioscience, 2013)
Glioblastomas are grade IV brain tumors characterized by high aggressiveness and invasiveness, giving patients a poor prognosis. We investigated the effects of the multi-kinase inhibitor sorafenib on six cultures isolated from human glioblastomas and maintained in tumor initiating cells-enriching conditions. These cell subpopulations are thought to be responsible for tumor recurrence and radio- and chemo-resistance, representing the perfect target for glioblastoma therapy. Sorafenib reduces proliferation of glioblastoma cultures, and this effect depends, at least in part, on the inhibition of PI3K/Akt and MAPK pathways, both involved in gliomagenesis. Sorafenib significantly induces apoptosis/cell death via downregulation of the survival factor Mcl-1. We provide evidence that sorafenib has a selective action on glioblastoma stem cells, causing enrichment of cultures in differentiated cells, downregulation of the expression of stemness markers required to maintain malignancy (nestin, Olig2 and Sox2) and reducing cell clonogenic ability in vitro and tumorigenic potential in vivo. The selectivity of sorafenib effects on glioblastoma stem cells is confirmed by the lower sensitivity of glioblastoma cultures after differentiation as compared with the undifferentiated counterpart. Since current GBM therapy enriches the tumor in cancer stem cells, the evidence of a selective action of sorafenib on these cells is therapeutically relevant, even if, so far, results from first phase II clinical trials did not demonstrate its efficacy.